Integration bile acid metabolomics and gut microbiome to study the anti-liver fibrosis effects of total alkaloids of Corydalis saxicola Bunting - Qianyi Wang; MeiLing Zhang; Mingwei Meng; Zhuo Luo; Ziping Pan; Lijun Deng; Jinghua Qin; Bingjian Guo; Dan Zhu; Yanmin Zhang; Hongwei Guo; Yonghong Liang; et al. (Chinese Medicine)
Abstract Background Bile acids and gut microbiota participate in the pathogenesis of liver fibrosis (LF). The total alkaloids of Corydalis saxicola Bunting (TACS) is a traditional Chinese medicine extract that has been used to treat LF, but the underlying mechanisms are not clear. This study performed integrated metabolomics and gut microbiome analysis to study the anti-LF mechanism of TACS using a rat model. Methods Ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS) was used to identify the chemical compounds in TACS. Biochemical and histopathological analysis were performed to determine the efficacy of TACS. Bile acid-targeted metabolomics was used to assess changes in the bile acid (BA) profiles in TACS-treated LF rats. 16S rRNA gene sequencing and metagenomics were used to assess changes in the gut microbiota of the TACS-treated LF rats. Antibiotic cocktail treatment and fecal microbiota transplantation (FMT) were used to determine the relationship between the gut microbiota and the anti-LF effects of TACS. Metagenomics was used to identify significantly enriched gut microbiota after TACS treatment and its correlation with the anti-LF effects was verified by in vivo experiments. Results TACS treatment significantly reduced the levels of serum liver enzymes, fibrosis and pro-inflammatory cytokines in the liver. TACS significantly increased the levels of chenodeoxycholic acid (CDCA) and taurochenodeoxycholic acid (TCDCA) in the cecum and decreased the levels of cholic acid (CA) and deoxycholic acid (DCA) in the liver of the LF rats. TACS significantly increased the abundances of Lactobacillus and Akkermansia in the LF rats. Antibiotic cocktail treatment and FMT have shown that the effect of TACS cure liver fibrosis depends on the gut microbiota. The abundance of Lactobacillus reuteri was significantly increased by TACS. Administration of Lactobacillus reuteri via gavage ameliorated LF. Conclusions TACS exerted anti-LF effects in rats by modulating bile acid metabolism and gut microbiome. Graphical Abstract